Gender and ethnic equity: what can we learn from ancestral and indigenous peoples to deal with socio-environmental issues? - Zank, Sofia; Hanazaki, Natalia; de Melo, Clarissa Rocha (Ethnobiology and Conservation, 2021)
The socio-environmental crisis that we are currently experiencing requires integrative research approaches and actions. Ethnobiology has important potential in this regard, both for its interdisciplinary nature and for recording the relationship between humans and the environment at different times and places. In this way, this opinion essay aims to discuss what we can learn from ancestral societies and Indigenous peoples for the establishment of a more equitable and sustainable world, considering the intersection between gender and ethnic groups. We will begin by examining the history of societies in Old Europe and how domineering and patriarchal societies have been established. We will discuss a few findings about pre-Columbian peoples in America that reinforces the the existence of more equitable societies. We add discussions related to gender, in the context of Indigenous peoples, and reflecting on the importance of the feminine and of the complementarity in social relationships. Finally, we discuss the role of ethnobiological research in this context and the ways of collaborating to support values that favor the establishment of equitable societies, which are fundamental to address the challenges of this era of change.